The impact of electronic publishing the future for publishers and librarians - Brown, David J.; Boulderstone, Richard; Gale Group (Munchen, Germany K.G. Saur, 2008)
Provides practical data to support investment decisions in information systems for electronic media, quantifies the future size of the electronic publishing industry, and serves as an aid to forward planning.
Background -- Industry evolution -- End user behaviour -- Measuring the value of information -- Electronic information industry structure -- The key players -- Publication formats -- Legal developments -- Geographical trends -- Research disciplines -- Drivers for change -- Financial and administrative drivers -- Business models as driver for change -- Funding research as a driver for change -- Efficiency improvements as a driver for change -- Technology as a driver for change -- Data and datasets as a driver for change -- Mining of text and data -- E-science and cyberinfrastructure as drivers for change -- Workflow processes and virtual research environments -- The Semantic Web as a driver for change -- Mobile devices as driver for change -- Archiving and preservation as drivers for change -- Findability as a driver for change -- Web 2.0 and social collaboration as drivers for change -- Trust -- Timeline - emergence of electronic publishing -- Summary and recommendations.
Electronic reproduction.
Keywords: Electronic publishing; Libraries and electronic publishing; Digital media -- Management; Electronic books